2006
DOI: 10.1111/j.0014-3820.2006.tb01110.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Unisexuality in Calligrapha Leaf Beetles: Molecular and Ecological Insights on Multiple Origins via Interspecific Hybridization

Abstract: Abstract. Interspecific hybridization is a well-established cause of unisexual origins in vertebrates. This mechanism is also suspected in other apomictic taxa, but compelling evidence is rare. Here, we evaluate this mechanism and other hypotheses for the evolutionary origins of unisexuality through an investigation of Calligrapha leaf beetles. This group provides an intriguing subject for studies of unisexual evolution because it presents a rare insect example of multiple apomictic thelytokous species within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 66 publications
(78 reference statements)
0
36
0
Order By: Relevance
“…Bisexual species were represented by one external outgroup considered for phylogenetic tests (C. dislocata; see below) and 13 of 18 species belonging to the clade where unisexual taxa originated, including all potential parental evolutionary lineages (Gó mez-Zurita et al 2006).…”
Section: Taxon Samplingmentioning
confidence: 99%
See 3 more Smart Citations
“…Bisexual species were represented by one external outgroup considered for phylogenetic tests (C. dislocata; see below) and 13 of 18 species belonging to the clade where unisexual taxa originated, including all potential parental evolutionary lineages (Gó mez-Zurita et al 2006).…”
Section: Taxon Samplingmentioning
confidence: 99%
“…Yet in Calligrapha, the transition to unisexuality occurred many times independently, which makes it a very interesting evolutionary oddity, covered in the classical treatises on the evolution of sex (e.g., Maynard Smith 1978;Bell 1982). Unisexuality in Calligrapha has been unequivocally associated with tetraploidy (Robertson 1966), which likely arose via allotetraploidy (Gó mez- Zurita et al 2006). This, together with phylogenetic reasoning, suggests their hybrid origin.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent molecular studies on Coleoptera have revealed the complexity of the problem. It appears that, in a given species, both parthenogenesis and polyploidization can occur repeatedly and independently (Gómez-Zurita et al, 2006). As concluded by White & Contreras (1981), after an extensive study of the other parthenogenetic grasshopper Warramaba virgo "it is unlikely that the above questions can be answered in any simple universally valid manner".…”
Section: Introductionmentioning
confidence: 99%